Tests of the Specification of Univariate and Bivariate Ordered Probit - Butler, J. S.; Chatterjee, Patrali (The Review of Economics and Statistics, 1997)
This note presents tests of the specification of univariate and bivariate ordered probit. The test is sensitive to deviations from either normality or the exogeneity of the explanatory variables. As an example, the ownership of dogs and televisions, both sources of time-intensive entertainment, is studied. The specification for dogs is not rejected, the specification for televisions is rejected at the 2.0% level, and the specification of both together is rejected at the 1.3% level.